Identification of a natural recombination in the F and H genes of feline morbillivirus - Park, Eun-Sil; Suzuki, Michio; Kimura, Masanobu; Maruyama, Keiji; Mizutani, Hiroshi; Saito, Ryuichi; Kubota, Nami; Furuya, Tetsuya; Mizutani, Tetsuya; Imaoka, Koichi; Morikawa, Shigeru (Virology (New York, N.Y.), 2014)
Feline morbillivirus (FmoPV) has recently been identified in Hong Kong and Japan. FmoPV is considered to belong to the genus Morbillivirus, in the family Paramyxoviridae. In this study, the complete nucleotide sequences of three strains of FmoPV detected in cats in Japan were determined. Among the six genes in FmoPV; N, P/V/C, M, F, H and L, the P gene showed the highest polymorphism in the nucleotide and putative amino acid sequences among the FmoPV strains. There was no geographical association in terms of the FmoPV phylogeny; however, from extensive phylogenetic and recombination analyses, we found that one Japanese FmoPV strain, MiJP003, was a probable recombinant between two virus strains in the independent lineages found in Japan and Hong Kong, respectively. The recombination was considered to have occurred within the F and H genes. Such recombination is thought to be involved in the evolution of FmoPV. •Complete nucleotide sequence of 3 FmoPV strains are determined.•A possible recombination in F and H genes of FmoPV is found.•P gene shows the highest rate of polymorphism among 6 viral genes.